Des poussières et du temps, notion de temporalité hétérochrone chez Jacques Rancière et Jean-Marc Desgent - François Gagnon (Conserveries Mémorielles)
Relying on the collection Vingtièmes siècles of the poet Jean-Marc Desgent, I intend to verify the hypothesis of Jacques Rancière developed in Les mots de l’histoire, essai de poétique du savoir that scholarly history is nourished by words without fixed reference - heresy, revolution, democracy, bully, etc. – and seizes them in reference to specific events - the death of King Philip II, September 13, 1598 - briefly, it makes the history a few new tricks of literature. Invertedly, it also means that literature forge and product historical time. Thus, in the poetic collection Vingtièmes siècles, by multiplying the words "grave" and "dust", Jean-Marc Desgent built a fragmented temporality, gap, but habitable. Repeated evocation of dust and dizzy ellipsis characterize this heterochronous temporality of the twenty-first century, which experienced a jerky time with multiple accents that do not ignore the repetition and the duplication, as already indicated by the use of the plural in the title of the collection, Vingtièmes siècles.